1952
DOI: 10.2136/sssaj1952.03615995001600030008x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ammonium Nitrate Applications to Field Soils on Nodulation, Seed Yield, and Nitrogen and Oil Content of the Seed of Soybeans

Abstract: A 2‐year field study was conducted to determine the possibility of supplementing soil and symbiotically‐fixed nitrogen of soybeans with nitrogen fertilizer.In 1947, during a hot dry growing season marked responses were obtained from added nitrogen. The number of nodules per plant decreased 80 to 90%, there were appreciable increases in seed yields, nitrogen content of the seed increased, and oil content decreased.In 1949, with adequate rainfall, moderate temperatures, and 30 to 40 days additional growing seaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

1959
1959
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 0 publications
1
23
0
Order By: Relevance
“…This is similar to findings from Sadler and Karlen (1995), who reported sharp increases in the N uptake of corn during the onset of tasseling and milk stages (VT and R3 stages). Soybeans assimilated less than 10% of the 15 N fertilizer added, probably because they were well nodulated and did not require supplemental N. The negative feedback between N fertilization and N 2 fixation in nodules is well known (Lyons and Earley 1952), but a 24-h period may be insufficient to inhibit N 2 fixation and permit much uptake of 15 N-NO 3 . While not significant, there was a slight increase in 15 N in soybean shoots during the study period, consistent with the expected increase in shoot N during soybean growth (Sadler and Karlen 1995).…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to findings from Sadler and Karlen (1995), who reported sharp increases in the N uptake of corn during the onset of tasseling and milk stages (VT and R3 stages). Soybeans assimilated less than 10% of the 15 N fertilizer added, probably because they were well nodulated and did not require supplemental N. The negative feedback between N fertilization and N 2 fixation in nodules is well known (Lyons and Earley 1952), but a 24-h period may be insufficient to inhibit N 2 fixation and permit much uptake of 15 N-NO 3 . While not significant, there was a slight increase in 15 N in soybean shoots during the study period, consistent with the expected increase in shoot N during soybean growth (Sadler and Karlen 1995).…”
Section: Discussionmentioning
confidence: 99%
“…A few studies showed that small amounts of starter-N applied at sowing could improve root growth and N uptake by soybean prior to full nodulation (Hardarson & Zepata, 1984;Wani et al, 1995;Gulden & Vessey, 1998). Furthermore, positive responses to N fertilization have been reported when soybean yields are affected by drought (Lyons & Earley, 1952;Purcell & King, 1996). R. Bras.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, other researchers have not obtained yield increases from N applications (Thurlow and Hiltbold, 1970;Wagner and Fletchall, 1966), reporting that soybeans properly inoculated with effective strains of rhizobium need no additional N, because they can fix an adequate supply. The proportion of protein in soybean has also been found to increase with increasing N rates (Kapusta et al, 1970).A detrimental effect of N fertilizer on nodulation has also been reported, high N rates applied at planting time reducing nodulation (Gibson and Nutman, i960;Lyons and Earley, 1952;Orcutt and Wilson, 1934), though moderate amounts of N at planting have not completely eliminated nodulation (Kapusta et al). The objective of this study was to determine the effect of different N rates on the nodulation and productivity of soybeans.…”
mentioning
confidence: 99%